2023
DOI: 10.7554/elife.88189
|View full text |Cite
|
Sign up to set email alerts
|

Novel regulators of islet function identified from genetic variation in mouse islet Ca2+ oscillations

Abstract: Insufficient insulin secretion to meet metabolic demand results in diabetes. The intracellular flux of Ca2+ into β-cells triggers insulin release. Since genetics strongly influences variation in islet secretory responses, we surveyed islet Ca2+ dynamics in eight genetically diverse mouse strains. We found high strain variation in response to four conditions: 1) 8 mM glucose; 2) 8 mM glucose plus amino acids; 3) 8 mM glucose, amino acids, plus 10 nM GIP; and 4) 2 mM glucose. These stimuli interrogate β-cell fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Laboratory mice are a vital source of islets of Langerhans in beta cell physiology research; however, various laboratories employ various mouse models. Previous research has indicated that there is a considerable phenotypic variation between different mouse strains as well as substrains of the inbred strains [ 73 75 ] which manifest themselves also in beta cell responses to glucose and [Ca 2+ ] i signalling characteristics [ 33 , 76 ]. For that reason, we investigate here whether the functional beta cell network structure extracted from multicellular [Ca 2+ ] i recordings in tissue slices depends on the mouse strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory mice are a vital source of islets of Langerhans in beta cell physiology research; however, various laboratories employ various mouse models. Previous research has indicated that there is a considerable phenotypic variation between different mouse strains as well as substrains of the inbred strains [ 73 75 ] which manifest themselves also in beta cell responses to glucose and [Ca 2+ ] i signalling characteristics [ 33 , 76 ]. For that reason, we investigate here whether the functional beta cell network structure extracted from multicellular [Ca 2+ ] i recordings in tissue slices depends on the mouse strain.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, during the plateau phase, the encoding mechanisms to enhance calcium activity in response to glucose differ quantitatively in all three groups [ 33 ]. Secretagogues other than glucose also cause [Ca 2+ ] i oscillations to vary greatly [ 76 ]. Generally, however, there are similarities between C57BL/6J, C57BL/6N, and NMRI mice in the sense that all three groups showed glucose-dependent activation and deactivation responses, as well as a 3% increase in relative active time per millimole of glucose [ 33 ].…”
Section: Discussionmentioning
confidence: 99%